Lecture-Conversation in Methodological Instrumentation of Russian as a Foreign Language Teacher - T. G. Arkadyeva; M. I. Vasilyeva; S. S. Vladimirova; N. S. Fedotova; T. G. Sharri (Научный диалог, 2017)
The article justifies the urgency of development of lectures-conversations when presenting the theoretical material of the training courses to foreigners. Attention is drawn to the difficulties of foreign students in listening the lecture in its traditional understanding as a monologue of the teacher. The importance of a methodical understanding of the theoretical presentation of the material in question-answer form is emphasised. Scientific novelty and practical significance of research results is seen in the fact that the issues are described from the point of view of the purpose of their performance to the students, the positive effect of the issue, the shortcomings of the question. It is assumed that within this form of classes the teacher can introduce new material, systematize theoretical information studied by students, consolidate students’ knowledge in the subject area, take into account communicative and personal aspects of adaptation of foreign students in Russian educational environment. On the original author’s material of lecture-conversation on theoretical grammar the kinds of questions are demonstrated that are appropriate to use in dialogue with foreign students. Methodological training for teachers in the formulation of various types of questions is proposed. It is concluded that the systematic use of lecture-conversation in teaching practice will contribute to overcoming the communicative and psychological difficulties of foreign students listening to lectures in a foreign language (Russian) that meets the modern trends of multicultural education.